An Application-centric Perspective on Industrial Artificial Intelligence - Schmitz, Markus; Yesilbas, Dilara (AMCIS 2022 Proceedings, 2022)
Advances in Artificial Intelligence have made its application increasingly relevant to all types of Information Systems. One area where researchers and practitioners see massive potential is the interface between Artificial Intelligence-empowered Information Systems and industrial processes. This explicit area of Industrial Artificial Intelligence and Industry 4.0 has been a popular topic of recent work and has opened up new research streams and applications. However, given the increasing number of publications, it is difficult to discern where the research field is heading. In our work, we conduct a systematic literature review of 296 scientific articles to provide a comprehensive overview of the current state of Industrial Artificial Intelligence in terms of research streams and application areas. We present both a metadata analysis as well as an application-specific analysis. Our results reveal insights into 14 major application areas as well as several findings on applied algorithms and approaches of Artificial Intelligence.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Industrial Applications; Industrial Artificial Intelligence; Machine Learning; Systematic Literature Review